Pattern synthesis of distorted phased array antenna with unsteady surface deformation considering dynamic range ratio - Wang, Qi; Yu, Yuanxin; Pan, Yuning; Gao, Renjing; Liu, Shutian (International journal of microwave and wireless technologies, 2024)
This paper presents an optimization method for pattern synthesis of distorted phased array antenna with unsteady surface deformation considering the dynamic range ratio (DRR). In the synthesis approach, different array deformations under unsteady mechanical loads are considered, and the distorted distribution of array elements is calculated after solving the mechanical deformation model. Then, optimize the excitation coefficients of each array element including amplitude and phase with DRR control so as to recover a high-quality pattern from a deteriorated pattern caused by the unsteady deformations. The optimization objective is to minimize the peak sidelobe level, which is synthesized by using a gradient-based algorithm. The optimized excitations can be used as the initial excitation, and the corresponding phase excitations can be derived according to the different deformations.